2015
DOI: 10.1177/2325957415601503
|View full text |Cite
|
Sign up to set email alerts
|

Features of Metabolic Syndrome and Its Associated Factors during Highly Active Antiretroviral Therapy in Ouagadougou (Burkina Faso)

Abstract: Cardiovascular risks should be regarded during the care of HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 19 publications
6
19
0
4
Order By: Relevance
“…Associated factors were PI regimens, female sex, age >42 years ( p =0.001) and lipodystrophy ( p =0.01). 64 …”
Section: Methodsmentioning
confidence: 99%
“…Associated factors were PI regimens, female sex, age >42 years ( p =0.001) and lipodystrophy ( p =0.01). 64 …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, hyperglycemia was observed in 18% of patients (including 12% diabetes) versus 4% in untreated subjects (including 2% diabetes), p < 0.0001. Guira O. in Burkina Faso found that 29.6% of subjects had hyperglycemia [7]. Likewise the lipid profile of subjects treated is different from that of untreated: 44% had hypercholesterolemia versus 13%, p = 0.02.…”
Section: Discussionmentioning
confidence: 95%
“…Bilirrubin elevation is a known adverse effect of atazanavir during pregnancy or anytime of use. It is known that protease inhibitors can cause lipid metabolic changes, metabolic syndrome, lipodystrophy, changes in the carbohydrate metabolism and increased cardiovascular risk in every HIV infected patient [ 47 49 ]. Some studies had demonstrated that during pregnancy women in use of PI also presented higher rates of dyslipidemia, metabolic syndrome, lipodystrophy, diabetes and pre-eclampsia [ 50 – 52 ], as some of our data also demonstrated.…”
Section: Discussionmentioning
confidence: 99%